Research on variable bus voltage control algorithm of axial flux stator coreless permanent magnet motor - Xiaoguang WANG; Yifan ZHOU; Mengkai CHEN; Yahong CHEN (Journal of Hebei University of Science and Technology)
Aiming at the problem of large stator current fluctuation and poor peak controllability caused by small winding inductance of coreless axial flux permanent magnet motor, a variable bus voltage control strategy was proposed by deducing the mathematical relationship between the DC bus voltage and the peak value of stator current fluctuation, which reduces the difference between the DC bus voltage on the inverter bridge side and the back EMF under actual working conditions. The minimum value of the bus voltage was determined according to the actual speed and electromagnetic torque, and the maximum value of the bus voltage was set by combining the maximum current ripple allowable value and the back electromotive force. On this basis, the optimal voltage algorithm was used to obtain the optimal value of the DC bus voltage of the inverter. The simulation and experimental results show that the optimal voltage algorithm and variable bus voltage control strategy proposed can significantly improve the current waveform, effectively reduce the fluctuation and peak value of stator current, and provide strong support for the performance optimization of axial flux stator coreless permanent magnet motor.